Antioxidant and Anti-Mutagenic Potential of Mint (Mentha Arvensis) and its Chemical Characterization by HPLC - Wardah Rashid, Shazia Asim, Shazma Rashid, Shakeela Rafique, Rao Salman Aziz, Salman Iftikhar, Muhammad Rashid, Yasir Arfat (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mentha arvensis has been used for medicinal purposes by Asian countries for ages. It is used to cure various ailments such as diarrhea, asthma, piles, cancer, dementia, hyperglycemia, and aging. Aim: This study aims to evaluate the antioxidant and anti-mutagenic (geno-protective) properties of four different solvent extracts (methanol, ethanol, acetone, and distilled water). Methodology: The antioxidant properties were determined by DPPH and reducing power assays, while the DNA damaging assay was used to evaluate the anti-mutagenic activity. Results: Among the four extracts, the methanol extract of Mentha arvensis showed 30.48 ± 0.95 mg QE/gm of flavonoid, and the aqueous extract showed the highest total phenolic content (142.2±0.83 mg QE/gm) and total alkaloids content (78.2±0.21 mg TE/gm) compared to the other three solvent extracts. The ethanol extract of Mentha arvensis exhibited the maximum value for total tannin content (17.41±0.38 mg ETA/g CE) and reducing power (41.17±0.87 mg ETA/gm). It also exhibited significant geno-protective activity. Conclusion: These results indicate that among the four solvent extracts, the ethanolic extract of Mentha arvensis has the highest value for phenolic content. Moreover, all four solvents, except distilled water, showed valuable anti-mutagenic behavior. The HPLC results corroborate our findings, suggesting that these plants have great potential for use as antioxidant and anti-mutagenic agents. Keywords: Mentha arvensis, Antioxidant agents, Anti-mutagenic agents, Geno-protective activity.